Grid-connected solar irrigation in Nepal - exploring opportunities and identifying hurdles - Shrestha, Shisher; Gnawali, S. M.; Mukherji, Aditi (International Water Management Institute, 2023)
The Alternative Energy Promotion Centre (AEPC) offers subsidies for off-grid Solar Irrigation Pumps (SIPs) to promote sustainable irrigation practices. The utilization of these off-grid SIPs is low due to irrigation demand patterns. The potential for gridconnected solar irrigation is increasing as Nepal's national utility grid network grows. Nevertheless, despite net metering regulations, off-grid SIPs are not integrated into the national grid. The Swiss Agency for Development and Cooperation (SDC) is implementing a pilot project called Solar Irrigation for Agriculture Resilience in South Asia (SoLAR-SA). The project aims to explore gridconnected solar irrigation and answer policy questions on the best techno-institutional model for grid integration in Nepal. Collaboration among major stakeholders during the implementation of pilot projects will contribute to developing guiding policies for grid-connected solar irrigation. Establishing specific policies for net metering targeted at agriculture meters is crucial for the scalability of grid-connected solar irrigation.